Ataxia and Homeopathy - Rai, Satya Prakash; Khare, Anshita; Rai, Ashutosh (Journal for Research in Applied Sciences and Biotechnology, 2024)
Ataxia is a neurological sign that manifests lack of coordination in the movement of different muscles in the body[1]. Ataxia is a term for a group of disorders that affect co-ordination, balance and speech. The exact symptoms and their severity vary depending on the type of ataxia person has. Homeopathic treatment is based on the Totality of Symptoms in each case. Today Homoeopathy is unique system of medicine as it takes a holistic approach towards the sick individual through enhance the inner balance at mental, physical, emotional, and spiritual levels. There are many effective medicines available in Homoeopathy for Ataxia, but the selection depends upon the individuality of the patient, considering mental and physical symptoms.